Gender Budgeting : Fiscal Context and Current Outcomes - Stotsky, Janet (IMF Working Papers; Working Paper ;, 2016)
Gender budgeting is an approach to budgeting that uses fiscal policy and administration to promote gender equality and girls and women's development. This paper posits that, properly designed, gender budgeting improves budgeting, and it places budgeting for this purpose in the context of sound budgeting principles and practices. The paper provides an overview of the policies and practices associated with gender budgeting as they have emerged across the world, as well as examples of the most prominent initiatives in every region of the world. Finally, it suggests what can be learned from these initiatives.